An Approach To The Development of Hybrid Object-Oriented Design Tool - Sitiol, Augustina Aegidius; Lee, Sai Peck (Malaysian Journal of Computer Science, 1999)
The design and development of systems are confronted with objects involving a great variety of notations [1]. Objects identified within the problem can be represented in the software solution. Thus object design methods involve constructing an object-oriented model of the problem and mapping this model into a software design [2]. In this paper, Hybrid Object-oriented Method (HOOM) [3] is chosen whose concepts and techniques will be introduced briefly. HOOM is an object-oriented software development methodology [3] with graphical notations1 representing object-oriented concepts. HOOM focuses on modeling of objects. The use of CASE tools could improve the ability to generate timely, quality software [4] using HOOM. CASE, which is an abbreviation for Computer-Aided Software Engineering, is a technology to automate software development. The need for a development of a new CASE tool, ODT (Hybrid Object-oriented Design Tool) to construct the object diagrams and other diagrams is defined. In contrast to many of the currently available tools, this project is intended to encourage the use of HOOM. Mapping of objects to a common form for integration of the represented knowledge and consistency checking is described.